2020
DOI: 10.1017/s0714980820000070
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hearing, Vision, and Dual Sensory Loss in Older Canadians: An Analysis of Data from the Canadian Longitudinal Study on Aging

Abstract: The purpose of this study was to describe the prevalence of hearing loss (HL), vision loss (VL), and dual sensory loss (DSL) in Canadians 45–85 years of age. Audiometry and visual acuity were measured. Various levels of impairment severity were described. Results were extrapolated to the 2016 Canadian population. In 2016, 1,500,000 Canadian males 45–85 years of age had at least mild HL, 1,800,000 had at least mild VL, and 570,000 had DSL. Among females, 1,200,000 had at least mild HL, 2,200,000 had at least mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 73 publications
2
33
0
1
Order By: Relevance
“…Diagnosis of mood disorder was associated with a trivial to small increased likelihood of cognitive impairment, consistent with meta-analyses demonstrating a small magnitude of association between depression and cognition (43). Similarly sensory loss had a trivial to small association with cognitive impairment, consistent with associations reported between cognition and sensory function (44). Bowel incontinence was associated with increased risk of cognitive impairment, potentially due to comorbidities of bowel incontinence with some neurological conditions (e.g., more advanced dementia); alternatively, this nding could be related to a possible link between bowel disorders and cognition via the vagus nerve (45).…”
Section: Discussionsupporting
confidence: 77%
“…Diagnosis of mood disorder was associated with a trivial to small increased likelihood of cognitive impairment, consistent with meta-analyses demonstrating a small magnitude of association between depression and cognition (43). Similarly sensory loss had a trivial to small association with cognitive impairment, consistent with associations reported between cognition and sensory function (44). Bowel incontinence was associated with increased risk of cognitive impairment, potentially due to comorbidities of bowel incontinence with some neurological conditions (e.g., more advanced dementia); alternatively, this nding could be related to a possible link between bowel disorders and cognition via the vagus nerve (45).…”
Section: Discussionsupporting
confidence: 77%
“…In addition to dementia risk, hearing loss is also associated with higher rates of hospitalization/rehospitalization with longer hospital stays, frailty, depression, loneliness, social isolation, and the onset of overt behavioral symptoms in long term care [8][9][10][11][12][13][14][15][16][17]. Hearing loss is more frequent in males than females, and the use of hear-ing aids also differs by sex [18][19][20]. These findings…”
Section: Introductionmentioning
confidence: 99%
“…Studies on DSL have shown to be prevalent among older adults. A Canadian study, analyzing data from the Canadian Longitudinal Study on Aging showed that 25% of the adults 70–75 years of age had DSL and the number is increasing, 10 something that, as already mentioned, can cause both depression and reduced quality of life in addition to functional disability. 11 …”
Section: Discussionmentioning
confidence: 95%
“…A Canadian study, analyzing data from the Canadian Longitudinal Study on Aging showed that 25% of adults 70–75 years of age had DSL and the number is increasing. 10 According to Jaiswal et al, DSL has been found to be the strongest predictor of functional disability and might increase the likelihood of depression and reduced quality of life. 11 …”
Section: Introductionmentioning
confidence: 99%